". . . The Forgotten Heroes": A Qualitative Study Exploring How Friends and Family Members of DV Survivors Use Domestic Violence Helplines. Issue 21 (November 2021) - Gregory, Alison; Taylor, Anna Kathryn; Pitt, Katherine; Feder, Gene; Williamson, Emma
Many women who experience domestic violence (DV) seek support from friends, relatives, colleagues, and neighbors. There are substantial knock-on effects for informal supporters, and they may seek help themselves. Tailored services for this group are rare, but DV helplines can provide listening and signposting support. The aim of this exploratory study was to understand which informal supporters contact DV helplines and what form these calls take. Three focus groups, following a topic guide, were conducted with staff and volunteers for DV helplines during autumn 2015. Discussions were digitally recorded, transcribed verbatim, and imported into NVivo10 software. Transcripts were coded line-by-line, and a thematic analysis carried out. All participants were female, aged between 22 and 54 years, with between 2 months' and 8 years' experience of taking helpline calls. Findings indicate that people with broad ranging connections to a survivor call a helpline. Calls can be triggered by disclosures, abuse escalation, witnessing incidents, feeling overwhelmed, and media highlighting of DV. Informal supporters respond to survivors, and experience impacts, in differing ways, often associated with their gender and their relationship with the survivor. Frequently, they feel a sense of responsibility and a desire to rescue the survivor, often calling a helpline to reduce feelings of helplessness and to seek a "magic" solution. Many people are concerned about the legitimacy of their involvement and seek reassurance about the validity of their own help-seeking. Helpline workers feel that informal supporters would benefit from opportunities to reduce isolation, have their predicament acknowledged, and learn from peers. DV helplines have an important role in helping informal supporters of survivors. The help requested is predominantly to equip and empower the informal supporter, so that they feel more adept at coping themselves and, are thus, better able to offer support to the survivor.